2018
DOI: 10.1038/s41598-018-27101-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke kinematic analysis in rats reveals similar reaching abnormalities as humans

Abstract: A coordinated pattern of multi-muscle activation is essential to produce efficient reaching trajectories. Disruption of these coordinated activation patterns, termed synergies, is evident following stroke and results in reaching deficits; however, preclinical investigation of this phenomenon has been largely ignored. Furthermore, traditional outcome measures of post-stroke performance seldom distinguish between impairment restitution and compensatory movement strategies. We sought to address this by using kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 65 publications
3
55
0
Order By: Relevance
“…In a recent study, we used kinematic analysis in rats with injury similar to the combined group (ie, cortical + striatal) in this study and found evidence for poststroke compensatory movement patterns similar to those exhibited by stroke patients. 44 Compensation may also exist in other tasks such as the beam and cylinder tests where animals may be making subtle changes in posture and forelimb movements. It remains to be seen how compensatory patterns vary with lesion location or in response to recovery-promoting interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we used kinematic analysis in rats with injury similar to the combined group (ie, cortical + striatal) in this study and found evidence for poststroke compensatory movement patterns similar to those exhibited by stroke patients. 44 Compensation may also exist in other tasks such as the beam and cylinder tests where animals may be making subtle changes in posture and forelimb movements. It remains to be seen how compensatory patterns vary with lesion location or in response to recovery-promoting interventions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, motor maps can be categorized in complex multiplanar movements such as abduction and adduction (Harrison et al, 2012; Bonazzi et al, 2013). Additionally, post-stroke emergence of abnormal movements or synergies in rats suggests that relearning may involve motor map reorganization to generate functional control of such complex movements (Balbinot et al, 2018). In our opinion this may not always be reflected by a greater size of motor representation, but to its content, such as the combination of different cortical modules for efficient post-stroke compensation.…”
Section: Two Phases Of Stroke Recovery – ‘Fast’ and ‘Slow’ Motor Relementioning
confidence: 99%
“…( B , left panels) Following stroke, diaschisis of regions close or distant to the infarct core (light blue) affects the functionality of the motor network and disrupts or change the specific action (red arrows: lost connections; blue and black arrows: remaining connections). ( B , right panels) This results in loss of upper motor neuron control over voluntary movements and the emergence of abnormal movements (Balbinot et al, 2018). Compensatory relearning is unlikely to fully restitute movements of the paretic limb, which should retain some of the abnormalities and deficits in the specific action.…”
Section: Diaschisis As a Consolidation-reconsolidation Processmentioning
confidence: 99%
“…While working with Dr. Dale Corbett and Dr. Diane Lagace at the University of Ottawa -Canada, we were pioneers in developing a kinematics-based framework to describe the motor impairments following a stroke in rodents. This work showed the first quantitative description of the "classical" flexor synergy in rodents (Balbinot et al, 2018). We believe the detailed description of movement impairment and recovery using kinematics holds the key to increase the translation of findings from animal models to the clinic.…”
mentioning
confidence: 78%